Conductive paste and preparation method and application thereof
In the preparation process of the conductive paste of carbon nanotubes, the mixed dispersion method of the modified solution and the carbon nanotubes was successfully improved, the carbon nanotube content was solved, and the problem of low carbon tube content in the prior art was achieved, and the cost reduction and efficiency improvement effect was achieved.
Patent Information
- Application Number
- CN202411879540.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
AI Technical Summary
The existing carbon nanotube conductive paste preparation methods cannot effectively increase the carbon tube content, resulting in high production costs and low transportation efficiency.
In an oxygen-containing atmosphere, the polyvinylpyrrolidone solution was treated with stirring and oxidation to prepare a modified solution, and then mixed with carbon nanotubes and dispersed to prepare a conductive paste with a mass content of 18%-20%.
The carbon nanotube content of the conductive paste is improved, the production cost is reduced, the transportation efficiency is improved, and the process is simple and easy to implement.
Smart Images

Figure CN119763927A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive paste, and in particular to a conductive paste and a preparation method and application thereof. Background Art
[0002] As energy and environmental issues become increasingly prominent, the development of electric vehicles is imperative. Among them, lithium-ion batteries have higher energy density and higher specific power, and are recognized as the most promising electric vehicle power batteries. Lithium-ion batteries generally include positive electrodes, negative electrodes, and separators between the positive and negative electrodes. The positive electrode sheet includes a positive electrode collector and a positive electrode film coated on the positive electrode collector, and the negative electrode sheet includes a negative electrode collector and a negative electrode film coated on the negative electrode collector. When preparing the electrode sheet, the active material, conductive agent, adhesive and solvent are first made into an electrode slurry, which is then coated on the surface of the current collector as required, and then dried to obtain a battery electrode sheet. Therefore, the performance of the conductive slurry has a great influence on the battery electrode sheet, and the performance of the conductive agent directly affects the performance of the electrode slurry.
[0003] At present, the conductive materials commonly used in lithium-ion battery conductive agents are carbon nanotubes, graphene and carbon black. Among them, carbon nanotube conductive paste, as a new type of lithium-ion battery conductive agent, can effectively improve the conductivity of lithium-ion batteries. The addition amount is 60% to 70% less than that of conventional carbon black conductive agents. At the same time, it can effectively reduce the amount of adhesive, which has a significant effect on improving the energy density of lithium-ion batteries. At present, the preparation method of carbon nanotube conductive paste in my country has become mature, and various preparation methods are emerging in an endless stream. However, looking at the preparation methods of these conductive pastes, they generally have the problem of low carbon tube content. Because carbon nanotubes have strong van der Waals forces between each other, they will entangle and aggregate together, and the traditional polyvinyl pyrrolidone (PVP) dispersant has limited dispersing ability. Under the condition of keeping the slurry at a low viscosity (<3000mPa s), the existing preparation method of carbon nanotube conductive paste cannot prepare non-aqueous carbon nanotube conductive paste with a carbon tube content exceeding 12%. Increasing the carbon nanotube content of carbon nanotube conductive paste is of great significance in reducing the production cost of paste and improving the transportation efficiency of paste, which is a difficult point in the preparation technology of carbon nanotube conductive paste. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a conductive paste and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a method for preparing a conductive paste, comprising: in an oxygen-containing atmosphere, stirring and oxidizing a 5%-10% polyvinyl pyrrolidone solution at 100°C-150°C to obtain a modified solution; mixing and dispersing the modified solution with carbon nanotubes to obtain a conductive paste; wherein the carbon nanotube mass content of the conductive paste is 18%-20%.
[0006] Optionally, the oxygen concentration in the oxygen-containing atmosphere is 10%-100%.
[0007] Optionally, the solvent in the polyvinyl pyrrolidone solution includes one of N-methylpyrrolidone and dimethylformamide.
[0008] Optionally, the molecular weight of polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 40,000-55,000.
[0009] Optionally, the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0010] Optionally, the carbon nanotube has a diameter of 10 nm-60 nm.
[0011] Optionally, the conductive paste further comprises graphite powder with a particle size of 50 nm-2 μm, and the mass content of the graphite powder is 0.1%-7%.
[0012] Optionally, the polyvinyl pyrrolidone solution is stirred and reacted at 100° C.-150° C. for 0.5 h-12 h.
[0013] Optionally, the polyvinyl pyrrolidone solution is stirred at 100° C.-150° C. and at a rotation speed of 100 rpm-300 rpm for reaction.
[0014] Optionally, the polyvinyl pyrrolidone solution is stirred at 100° C.-150° C. and 0.5 atm-1.5 atm.
[0015] Optionally, polyvinyl pyrrolidone is dissolved in the modified solution by stirring to prepare a mixed solution.
[0016] Optionally, the modified solution is mixed with a polyvinyl pyrrolidone solution to prepare a mixed solution.
[0017] Optionally, the mass ratio of the un-stirred oxidized polyvinyl pyrrolidone to the stirred oxidized polyvinyl pyrrolidone in the mixed solution is 1:(0.1-6).
[0018] Optionally, the modified solution and the carbon nanotubes are dispersed by ball milling.
[0019] Optionally, the modified solution is homogenized with the carbon nanotubes under high pressure.
[0020] Optionally, the modified solution is ultrasonically mixed with the carbon nanotubes.
[0021] In a second aspect, the present invention also provides a conductive paste prepared by any of the above optional preparation methods.
[0022] In a third aspect, the present invention further provides the use of the conductive paste prepared by any of the above optional preparation methods.
[0023] Optionally, the application includes mixing with active materials and then curing and molding on the surface of current collector to obtain battery pole pieces. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A flowchart of a method for preparing a conductive paste provided by the present invention;
[0025] Figure 2 This is a scanning electron microscope image of the conductive paste prepared in Example 1 of the present invention after curing and forming a film;
[0026] Figure 3 This is a scanning electron microscope image of the conductive paste obtained in Example 2 of the present invention after curing and forming a film;
[0027] Figure 4 This is a scanning electron microscope image of the conductive paste obtained in Example 3 of the present invention after curing and forming a film;
[0028] Figure 5 This is a scanning electron microscope image of the conductive paste obtained in Example 4 of the present invention after curing and forming a film;
[0029] Figure 6 This is a scanning electron microscope image of the conductive paste obtained in Example 5 of the present invention after curing to form a film;
[0030] Figure 7 This is a graph showing the dynamic viscosity change of the conductive paste obtained in Example 1 of the present invention from 0d to 180d;
[0031] Figure 8 This is a resistivity test diagram of the conductive paste prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0033] See also Figure 1 The present invention provides a method for preparing a conductive paste, comprising the following steps:
[0034] S1. Stirring and oxidizing the polyvinyl pyrrolidone solution in an oxygen-containing atmosphere to obtain a modified solution;
[0035] S2. Mix and disperse the modified solution and carbon nanotubes to obtain a conductive slurry.
[0036] In fact, by stirring and oxidizing the polyvinyl pyrrolidone in step S1, the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution can be partially oxidized, thereby obtaining oxidized polyvinyl pyrrolidone. In addition, oxidative modification of polyvinyl pyrrolidone in a solution environment can provide good protection for polyvinyl pyrrolidone, thereby preventing the polyvinyl pyrrolidone from being completely oxidized and becoming ineffective at high temperatures.
[0037] In fact, after the modified solution is prepared by stirring in step S1, the polyvinyl pyrrolidone after oxidation treatment in the modified solution can be used as a dispersant, and then after being mixed with carbon nanotubes in step S2, the carbon nanotubes can be evenly distributed, thereby obtaining a uniform and stable conductive paste. In addition, the preparation method provided by the present invention has a simple process and a low production cost.
[0038] Specifically, in step S1, the polyvinyl pyrrolidone solution is stirred and oxidized at 100° C.-150° C. In fact, the polyvinyl pyrrolidone solution can be heated in an oven or oil bath environment at 100° C.-150° C. The reaction activity of the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution can be increased by placing it in a high temperature environment, and the polyvinyl pyrrolidone solution can also play a protective role, thereby partially oxidizing the polyvinyl pyrrolidone.
[0039] Specifically, the concentration of the polyvinyl pyrrolidone solution used in step S1 is 5%-10%. In fact, by adjusting the concentration of the polyvinyl pyrrolidone solution, the oxidation modification rate in the stirring oxidation stage can be adjusted, thereby adjusting the dispersion performance of the obtained modified solution on carbon nanotubes. In addition, the molecular weight of the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution used is 40000-55000.
[0040] In some embodiments, the solvent of the polyvinyl pyrrolidone solution used in step S1 includes one of N-methyl pyrrolidone and dimethylformamide. In fact, the solvent of the polyvinyl pyrrolidone solution must be able to fully dissolve the polyvinyl pyrrolidone and be able to mix with the carbon nanotubes to form a usable conductive paste.
[0041] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere used in step S1 is 10%-100%. Specifically, the oxygen-containing atmosphere can be air or pure oxygen. In fact, when reacting in the oxygen-containing atmosphere, the liquid environment of the polyvinyl pyrrolidone solution can form a gas-liquid interface layer with the oxygen-containing atmosphere, and the degree of oxidation and oxidation reaction of the polyvinyl pyrrolidone can be controlled in this interface layer. In fact, the properties of solid polyvinyl pyrrolidone are relatively stable, and it is easy to self-crosslink and form an insoluble cross-linked polymer when heated at 100°C-150°C.
[0042] In some embodiments, in step S1, the polyvinyl pyrrolidone solution is stirred at 100° C.-150° C. for 0.5 h-12 h. In addition, during the stirring reaction, the stirring speed is controlled to be 100 rpm-300 rpm. At the same time, the polyvinyl pyrrolidone solution can be stirred in a pressure environment of 0.5 atm-1.5 atm.
[0043] In some embodiments, the carbon nanotubes used in step S2 include single-walled carbon nanotubes and multi-walled carbon nanotubes, and the diameter of the carbon nanotubes is 10nm-60nm. In fact, by adding carbon nanotubes into the modified solution, the partially oxidized polyvinyl pyrrolidone dissolved in the modified solution can be used as a dispersant to promote the uniform dispersion of the carbon nanotubes, thereby forming a uniform and stable conductive paste. Specifically, the mass content of carbon nanotubes in the conductive paste prepared in step S2 is 18%-20%.
[0044] In some embodiments, the conductive paste prepared in step S2 further includes graphite powder with a particle size of 50 nm-2 μm, and the mass content of the graphite powder in the conductive paste is 0.1%-7%. Specifically, by adding the graphite powder and the carbon nanotubes into the conductive paste, the graphite powder can be filled between the carbon nanotubes and further increase the solid content of the conductive paste.
[0045] In some embodiments, the graphite powder is mixed with the modified solution in advance when performing step S2, so as to obtain a mixed suspension in which the graphite powder is pre-dispersed. In fact, the graphite powder can be mechanically ball-milled in advance to improve the particle size uniformity and surface defects of the graphite powder, thereby facilitating the uniform dispersion of the graphite powder in the modified solution. Specifically, physical dispersion methods such as ball milling, high pressure homogenization, and ultrasonic dispersion can be used to promote the uniform dispersion of the graphite powder in the modified solution.
[0046] In some embodiments, when executing step S2, the polyvinyl pyrrolidone solid powder is stirred and dissolved in the modified solution to prepare a mixed solution. The mixed solution thus prepared contains partially oxidized polyvinyl pyrrolidone and unoxidized polyvinyl pyrrolidone, so that the dispersibility of the prepared conductive paste can be further improved and its viscosity can be reduced after the two are compounded.
[0047] In some embodiments, the modified solution and the polyvinyl pyrrolidone solution may be mixed in advance to obtain a mixed solution when performing step S2. In fact, the polyvinyl pyrrolidone solution used is the same as the polyvinyl pyrrolidone solution used in preparing the modified solution.
[0048] Specifically, when the mixed solution is prepared before step S2, the mass ratio of the un-stirred oxidized polyvinyl pyrrolidone to the stirred oxidized polyvinyl pyrrolidone in the mixed solution is 1:(0.1-6). In addition, in step S2, the mixed solution is mixed and dispersed with carbon nanotubes to obtain a conductive paste.
[0049] In some embodiments, in step S2, the modified solution and the carbon nanotubes are dispersed by ball milling. Zirconia balls with a diameter of 0.1 mm can be used as ball milling balls in a ball mill disperser, and the modified solution and the carbon nanotubes are dispersed by ball milling at a rotation speed of 200 rpm-400 rpm for 2h-10h. This can enable the modified solution to fully infiltrate the surface of the carbon nanotubes and improve the dispersion uniformity.
[0050] In some embodiments, in step S2, the modified solution and the carbon nanotubes are homogenized under high pressure, and the dispersion can be performed 5 to 20 times at a pressure of 100 MPa to 200 MPa in a high pressure homogenizer, thereby obtaining a uniform and stable conductive paste.
[0051] In some embodiments, in step S2, the modified solution and the carbon nanotubes are ultrasonically dispersed at an ultrasonic power of 400W-600W for 5h-8h, and intermittent ultrasonic treatment is used during the ultrasonic process and ice-water bath cooling is performed during the intervals of ultrasonic treatment.
[0052] Example 1
[0053] This embodiment 1 provides a method for preparing a conductive paste, comprising the following steps:
[0054] S0, dissolving 8 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 8%;
[0055] S1. In an air atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 140°C and stirred at 200 rpm for 2 hours, then taken out and cooled to room temperature to obtain a modified solution; 4 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0056] S2. Add 18 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model MCN4301) into the mixed solution, ultrasonically treat at 400 W ultrasonic frequency for 8 hours, and ice-bath for 10 minutes after each ultrasonic treatment; after ultrasonic treatment, a conductive slurry with a carbon nanotube content of 18 wt.% was obtained.
[0057] Example 2
[0058] This embodiment 2 provides a method for preparing a conductive paste, comprising the following steps:
[0059] S0, dissolving 6 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 6%;
[0060] S1. In an air atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 125°C and stirred at 200 rpm for 8 hours, then taken out and cooled to room temperature to obtain a modified solution; 1 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0061] S2. Add 19 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the mixed solution, mix, and put into a ball mill. Use zirconia balls with a diameter of 0.1 mm as ball milling balls. After ball milling at 300 rpm for 2 hours, a conductive slurry with a carbon nanotube content of 19 wt.% is obtained.
[0062] Example 3
[0063] This embodiment 3 provides a method for preparing a conductive paste, comprising the following steps:
[0064] S0, dissolving 6 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 6%;
[0065] S1. In an air atmosphere of 1 atm, the polyvinyl pyrrolidone solution was kept in an oil bath at 130°C and stirred at 200 rpm for 12 hours, then taken out and cooled to room temperature to obtain a modified solution; 4 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0066] Y1. Add 6 g of graphite powder with an average particle size of 100 nm into the mixed solution, mix, and put into a ball mill, use zirconia balls with a diameter of 0.1 mm as ball milling balls, and ball mill at 300 rpm for 10.5 h to obtain a mixed suspension;
[0067] S2. 18 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) were added to the mixed suspension and mixed, and then dispersed 5 times in a high-pressure homogenizer at a pressure of 150 MPa to obtain a conductive slurry with a carbon nanotube content of 18 wt.%.
[0068] Example 4
[0069] This embodiment 4 provides a method for preparing a conductive paste, comprising the following steps:
[0070] S0, dissolving 10 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 10%;
[0071] S1. In an oxygen atmosphere of 1 atm, the polyvinyl pyrrolidone solution was kept in an oil bath at 130°C and stirred at 200 rpm for 0.5 h, then taken out and cooled to room temperature to obtain a modified solution;
[0072] Y1. Add 6 g of graphite powder with an average particle size of 100 nm into the modified solution, mix, and put into a ball mill, use zirconia balls with a diameter of 0.1 mm as ball milling balls, and ball mill at 400 rpm for 9 hours to obtain a mixed suspension;
[0073] S2. Add 18 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the mixed suspension, mix, and then ultrasonically treat at 500 W ultrasonic frequency for 6.5 h, and ice-bath for 10 min after each ultrasonic treatment; after ultrasonic treatment, a conductive slurry with a carbon nanotube content of 18 wt.% was obtained.
[0074] Example 5
[0075] This embodiment 5 provides a method for preparing a conductive paste, comprising the following steps:
[0076] S0, dissolving 8 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 8%;
[0077] S1. In an oxygen atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 125°C and stirred at 200 rpm for 1 hour, then taken out and cooled to room temperature to obtain a modified solution; 2 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0078] Y1. Add 6 g of graphite powder with an average particle size of 100 nm into the mixed solution, mix, and put into a ball mill, use zirconia balls with a diameter of 0.1 mm as ball milling balls, and ball mill at 400 rpm for 9 hours to obtain a mixed suspension;
[0079] S2. Add 18 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the mixed suspension, mix, and then ultrasonically treat at 600 W ultrasonic frequency for 5 hours, and ice-bath for 10 minutes after each ultrasonic treatment; after ultrasonic treatment, a conductive slurry with a carbon nanotube content of 18 wt.% was obtained.
[0080] Example 6
[0081] This embodiment 6 provides a method for preparing a conductive paste, comprising the following steps:
[0082] S0, dissolving 8 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 8%;
[0083] S1. In an oxygen atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 110°C and stirred at 200 rpm for 4 hours, then taken out and cooled to room temperature to obtain a modified solution; 2 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0084] Y1. Add 6 g of graphite powder with an average particle size of 100 nm into the mixed solution, mix, and put into a ball mill, use zirconia balls with a diameter of 0.1 mm as ball milling balls, and ball mill at 400 rpm for 10 h to obtain a mixed suspension;
[0085] S2. Add 18 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the mixed suspension, mix and put into a ball mill, use zirconia balls with a diameter of 0.1 mm as ball milling balls, and mill at 300 rpm for 10 hours to obtain a conductive slurry with a carbon nanotube content of 18 wt.%.
[0086] Example 7
[0087] This embodiment 7 provides a method for preparing a conductive paste, comprising the following steps:
[0088] S0, dissolving 6 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 6%;
[0089] S1. In an air atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 110°C and stirred at 200 rpm for 4 hours, then taken out and cooled to room temperature to obtain a modified solution; 2 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0090] S2. Add 19 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the mixed solution, mix, and put into a ball mill. Use zirconia balls with a diameter of 0.1 mm as ball milling balls. After ball milling at 300 rpm for 10 hours, a conductive slurry with a carbon nanotube content of 19 wt.% is obtained.
[0091] Example 8
[0092] This embodiment 8 provides a method for preparing a conductive paste, comprising the following steps:
[0093] S0, dissolving 5 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 5%;
[0094] S1. In an oxygen atmosphere of 1 atm, a polyvinyl pyrrolidone solution was kept in an oil bath at 140°C and stirred at 200 rpm for 12 hours, then taken out and cooled to room temperature to obtain a modified solution; 10 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) was stirred and dissolved in the modified solution to obtain a mixed solution;
[0095] S2. 19 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) were added into the mixed solution and mixed. The mixture was dispersed 20 times in a high-pressure homogenizer at a pressure of 150 MPa to obtain a conductive slurry with a carbon nanotube content of 19 wt.%.
[0096] Example 9
[0097] This embodiment 9 provides a method for preparing a conductive paste, comprising the following steps:
[0098] S0, dissolving 8 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 8%;
[0099] S1. In an oxygen atmosphere of 1 atm, the polyvinyl pyrrolidone solution was kept in an oil bath at 125°C and stirred at 200 rpm for 8 hours, then taken out and cooled to room temperature to obtain a modified solution;
[0100] S2. Add 22 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the modified solution, mix, and put into a ball mill. Use zirconia balls with a diameter of 0.1 mm as ball milling balls. After ball milling at 300 rpm for 4 hours, a conductive slurry with a carbon nanotube content of 22 wt.% is obtained.
[0101] Example 10
[0102] This embodiment 10 provides a method for preparing a conductive paste, comprising the following steps:
[0103] S0, dissolving 8 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) in N-methyl pyrrolidone with stirring to prepare a polyvinyl pyrrolidone solution with a concentration of 8%;
[0104] S1. In an oxygen atmosphere of 1 atm, the polyvinyl pyrrolidone solution was kept in an oil bath at 140°C and stirred at 200 rpm for 4 hours, then taken out and cooled to room temperature to obtain a modified solution;
[0105] S2. Add 25 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model number MCN4301) into the modified solution, mix, and then put into a ball mill. Use zirconia balls with a diameter of 0.1 mm as ball milling balls. After ball milling at 300 rpm for 6 hours, a conductive slurry with a carbon nanotube content of 25 wt.% is obtained.
[0106] Performance Testing
[0107] After the conductive pastes in Examples 1 to 5 were coated and cured to form films, they were characterized using a scanning electron microscope. Figures 2 to 6 The conductive paste prepared in Example 5 was subjected to an adhesion test, and the viscosity curve was as follows: Figure 6 As shown; the viscosity change of the conductive paste prepared in Example 1 was measured at 0d-180d, as Figure 7 The conductive paste prepared in Example 1 was coated, and the thickness of the conductive paste coating was controlled to be 10 μm. After curing, a four-probe resistivity test was performed, and the results were as follows: Figure 8 shown.
[0108] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a conductive paste, characterized in that: include: In an oxygen-containing atmosphere, a polyvinyl pyrrolidone solution with a concentration of 5% to 10% is stirred and oxidized at 100° C. to 150° C. to obtain a modified solution; The modified solution and carbon nanotubes are mixed and dispersed to obtain a conductive paste; wherein the carbon nanotube mass content of the conductive paste is 18%-25%.
2. The preparation method according to claim 1, characterized in that: The oxygen concentration in the oxygen-containing atmosphere is 10%-100%; and / or, the solvent in the polyvinyl pyrrolidone solution includes one of N-methylpyrrolidone and dimethylformamide; and / or, the molecular weight of the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 40000-55000.
3. The preparation method according to claim 1, characterized in that: The carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes; and / or the carbon nanotubes have a diameter of 10nm-60nm; and / or the conductive paste also includes graphite powder with a particle size of 50nm-2μm, and the mass content of the graphite powder is 0.1%-7%.
4. The preparation method according to claim 1, characterized in that: The polyvinyl pyrrolidone solution is stirred and reacted at 100°C-150°C for 0.5h-12h; and / or, the polyvinyl pyrrolidone solution is stirred and reacted at 100°C-150°C at a rotation speed of 100rpm-300rpm; and / or, the polyvinyl pyrrolidone solution is stirred at 100°C-150°C and 0.5atm-1.5atm.
5. The preparation method according to claim 1, characterized in that: Before mixing the modified solution with the carbon nanotubes, the process includes: stirring and dissolving polyvinyl pyrrolidone in the modified solution to obtain a mixed solution; or mixing the modified solution with the polyvinyl pyrrolidone solution to obtain a mixed solution.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the un-stirred oxidized polyvinyl pyrrolidone to the stirred oxidized polyvinyl pyrrolidone in the mixed solution is 1:(0.1-6).
7. The preparation method according to claim 1, characterized in that: When the modified solution and the carbon nanotubes are mixed and dispersed, the steps include: dispersing the modified solution and the carbon nanotubes by ball milling; and / or homogenizing the modified solution and the carbon nanotubes by high pressure; and / or ultrasonically mixing the modified solution and the carbon nanotubes.
8. A conductive paste prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the conductive paste prepared by the preparation method according to any one of claims 1 to 7.
10. The use according to claim 9, characterized in that: The method comprises mixing with active materials and then curing and molding them on the surface of current collector to obtain battery pole pieces.